1999
DOI: 10.1063/1.124683
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube composite carbon fibers

Abstract: Current and Current and Current and Current and Current and recent past issues of Energeia recent past issues of Energeia recent past issues of Energeia recent past issues of Energeia recent past issues of Energeia may be viewed on the CAER Web

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
208
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(214 citation statements)
references
References 15 publications
4
208
0
2
Order By: Relevance
“…8 9 and the high thermal and electrical conductivity 10 of CNTs. Seven patents have already been issued for CNT nanocomposites and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…8 9 and the high thermal and electrical conductivity 10 of CNTs. Seven patents have already been issued for CNT nanocomposites and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…9 To take advantage of the extraordinary mechanical, electrical, and thermal properties of carbon nanotubes, several studies have been reported where attempts have been made to reinforce polymer and other matrix systems with carbon nanotubes. These studies include pitch/SWNT composite fiber, 10 polystyrene/MWNT (multiwall carbon nanotubes), 11 PMMA/SWNT, 12 and polypropylene/nanocarbon fiber. 13 While these studies confirm the potential benefits of reinforcing polymer and other matrices with carbon nanotubes, the challenge is to achieve good SWNT dispersion in the polymer and other matrices at significant nanotube weight fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent experiments on the preparation and mechanical characterization of CNT-polymer composites have also appeared. [2] [3] [4] These measurements suggest modest enhancements in strength characteristics of CNTembedded matrixes as compared to bare polymer matrixes. [4] Preliminary experiments and simulation studies on the thermal properties of carbon nanotubes show very high thermal conductivity.…”
mentioning
confidence: 99%
“…[2] [3] [4] These measurements suggest modest enhancements in strength characteristics of CNTembedded matrixes as compared to bare polymer matrixes. [4] Preliminary experiments and simulation studies on the thermal properties of carbon nanotubes show very high thermal conductivity. [5] It is expected, therefore, that nanotube reinforcements in polymeric materials may also significantly change the thermal and thermo-mechanical properties of the composites.…”
mentioning
confidence: 99%